THE INFLUENCE OF ACTIVITY PLANNING AND FINANCIAL MANAGEMENT POLICY IMPLEMENTATION ON BUDGET ABSORPTION EFFECTIVENESS THROUGH INTERNAL CONTROL AT THE MAKASSAR CITY LAND OFFICE - Herlyanty Sadik; Muspa Muspa; Muh.Ashary Anshar (Yayasan Education and Social Center, 2026)
This study aims to analyze the influence of Activity Planning and Financial Management Policy Implementation on Budget Absorption Effectiveness through Internal Control at the Makassar City Land Office. The research is motivated by the importance of budget absorption effectiveness in realizing accountable public financial governance and the differences in research results regarding the factors that influence it. The study used a quantitative approach with a survey method. The study population was 180 employees, while a sample of 112 respondents was determined using the Slovin formula. Data collection was carried out through questionnaires, then analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that Activity Planning did not significantly influence Internal Control or Budget Absorption Effectiveness. Conversely, Financial Management Policy Implementation had a positive and significant effect on Internal Control and Budget Absorption Effectiveness. Internal Control also had a positive and significant effect on Budget Absorption Effectiveness. In addition, Internal Control was unable to mediate the effect of Activity Planning on Budget Absorption Effectiveness, but was able to mediate the effect of Financial Management Policy Implementation on Budget Absorption Effectiveness. This finding confirms that the effectiveness of budget absorption is more determined by the implementation of financial management policies supported by effective internal controls.